2020
DOI: 10.3390/diagnostics10060381
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma Ameliorates Cyclophosphamide-Induced Acute Interstitial Cystitis/Painful Bladder Syndrome in a Rat Model

Abstract: Background: Interstitial cystitis/painful bladder syndrome (IC/PBS) could be treated to ameliorate urothelial injury. Here, we investigated the efficacy of intravesical instillation with platelet-rich plasma (PRP) and hyaluronic acid for acute IC/PBS. Methods: The effects of PRP and hyaluronic acid on the proliferation of normal human fibroblast cells (HFCs) were assessed. Additionally, thirty virgin female rats were randomized into five groups: group 1, saline-injected control; group 2, cyclophosphamide (CYP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Moreover, the expression of cell junction-associated protein zonula occludens 2 (ZO-2) was increased (p < 0.05) and the expression of IL-6 was decreased (p < 0.05) in group 4 compared to group 2. Furthermore, they showed that there was no synergistic effect when PRP and HA were administered together (p > 0.06), but rather PRP, due to its ability to express ZO-2, would play a predominant role in urothelial repair [17].…”
Section: Significant Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the expression of cell junction-associated protein zonula occludens 2 (ZO-2) was increased (p < 0.05) and the expression of IL-6 was decreased (p < 0.05) in group 4 compared to group 2. Furthermore, they showed that there was no synergistic effect when PRP and HA were administered together (p > 0.06), but rather PRP, due to its ability to express ZO-2, would play a predominant role in urothelial repair [17].…”
Section: Significant Resultsmentioning
confidence: 99%
“…The remaining plasma was centrifuged at 3000 rpm for 10 min. The supernatant was discarded, and approximately 1 mL of PRP was obtained from the buffy coat [16,17].…”
Section: Significant Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet-rich plasma helps not only in the management of urogynaecological problems but is handy in the diagnosis of certain conditions like painful bladder syndrome/interstitial cystitis. It has the potential to act as a modulator of urothelial repair, and this could be made useful in painful bladder syndromes [32]. Various research in the past couple of years is clearly suggestive of the fact that intravesical platelet-rich plasma reduces chronic inflammation in bladder pain syndrome/interstitial cystitis (BPS/IC) as they could improve regeneration of the urothelium [33].…”
Section: Plateletmentioning
confidence: 99%
“…Although hyperplasia is not a typical symptom of bladder pain syndrome, chronic systemic CYP injection in mouse models is still an important approach to study the underlying pathophysiology of bladder structures. However, rat bladder is more suitable for the study of bladder function, such as leak point pressure, as its capacity is more suitable than that of the mouse [ 37 ].…”
Section: Study Diseasesmentioning
confidence: 99%